Studi Kualitatif Pertumbuhan Populasi Kambing Paket Bantuan Crash Program dan Faktor yang Mempengaruhinya: Studi Kasus di Kampung Sekendi Distrik Teminabuan Kabupaten Sorong Selatan - Sraun, Thimotius (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2012)
Distribution of crash program-based local goat constitutes an object of agriculture policy of crash program implemented in 1995, and has done using members of Sekendi community village at district of Teminabuan of Sorong Selatan regency as targeted group. The program aimed to increase population of goat as the goal and the population of goat as subject. Village of Sekendi was chosen as visited sites. The finding of this research shown that population growth of goat is declining where thepopulation of goat and goat farmers are decreasing at 73.68% and 66,67%, respectively. Uncertainty of socio-economic and feeding ration, reproduction and management are factors determining population growth of goat. The failure of crash program based-goat is failed to achieve the goal.Key words: goat population, socio-economical factors, crash program, goat